SUITABILITY EVALUATION OF TEUPIN LAYEU IBOIH BEACH AS THE LOCATION OF MARINE ECOTOURISM - Dian Aswita; M. Ali Sarong; Sugianto Sugianto (Institute of Research and Community Services, Universitas Negeri Yogyakarta, 2015)
Teupin Layeu Iboih beach is one of the tourist locations in Sabang City and is one of the locations for marine tourism was developed from mass tourism to ecotourism. This research aimed to assess the suitability of Teupin Layeu Iboih beach as the location of marine ecotourism was carried out from March to June 2014. A descriptive approach was applied by using survey and fi eld observations. The parameters collected are the type of coral reefs, the coral fi sh species, the water depth, the water transparency, the type of beach, the coastal land cover, the bottom material, and the distance of freshwater availability from the beach. Research showed that Teupin Layeu Iboih beach is suitable for marine ecotourism as a recreational area with a value of 73% and very suitable for diving and snorkeling with a value of 86.7%.